CD4 bovine gene: Differential polymorphisms among cattle breeds and a new tool for rapid identification - Okino, Cintia Hiromi; Malagó Junior, Wilson; Marcondes, Cintia Righetti; Giglioti, Rodrigo; Montassier, Hélio José [UNESP]; Oliveira, Henrique Nunes de [UNESP]; Oliveira, Márcia Cristina de Sena (Elsevier, 2022)
Two mutations in the CD4 bovine gene (G>T/Q306H; A>C/K310N) were identified as causative for altered staining with anti-CD4 mAb #CC8. We developed a HRM qPCR for genotyping these mutations and compare with immunophenotyping in different cattle breeds. The assay distinguished five genotypes, B (homozygous, G/A) and C (heterozygous, G/A and T/C), found in taurine, A (homozygous, G/C) and D (heterozygous, T/C and G/C), found in zebu. The E genotype (homozygous, T/C) was not observed in tested animals. As expected, B and C presented high/very high and intermediate CD4 staining, respectively. The lack/low CD4 staining was mainly related to the A, while the intermediate staining was mainly related to D genotype. The developed HRM qPCR assay accurately identified the altered phenotypes associated with CC8 staining in taurine. However, the assay cannot be applicable in zebu or hybrid breeds, probably due to additional mutations in the CD4 gene from zebu descendant animals.
Keywords: Genotype; Immunophenotyping; QPCR, High Resolution Melt; T helper cells